Identification of Critical Factors Influencing Lean Construction Performance in Construction Projects - Devita Candraningtyas; I Putu Artama Wiguna (Journal La Multiapp, 2026)
The Indonesian construction sector continues to face persistent problems related to inefficiency, material waste, schedule delays, and cost overruns, despite increasing interest in adopting Lean Construction principles. These challenges indicate that lean implementation has not been fully supported by well-defined organizational and managerial foundations. This study aims to identify and validate the indicators that form the Critical Success Factors influencing Lean Construction Performance in high-rise building projects in Indonesia. This research uses quantitative methods. The research population consists of construction professionals involved in high-rise building projects, including contractors, consultants, and project management teams. A total of 360 questionnaires were distributed, of which 155 responses were returned. After data screening, 125 valid responses were used for further analysis. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares method through SmartPLS 3.0, focusing on the evaluation of the measurement model. The results indicate that the proposed constructs are formed by valid and reliable indicators after eliminating indicators with outer loadings below 0.70. The validated indicators represent management commitment and involvement, human resource development, communication and collaboration, internal client focus, and planning techniques and continuous improvement. These findings provide empirical evidence on the key indicator structure of Critical Success Factors relevant to Lean Construction Performance.